Response to targeted radionuclide therapy with [131I]MIBG AND [177Lu]Lu-DOTA-TATE according to adrenal vs. extra-adrenal primary location in metastatic paragangliomas and pheochromocytomas: A systematic review - Prado-Wohlwend, Stefan; del Olmo-García, María Isabel; Bello-Arques, Pilar; Merino-Torres, Juan Francisco (Frontiers in Endocrinology, 2022)
Purpose: Targeted radionuclide therapy (TRT) with [131I]MIBG and [177Lu]Lu-DOTA-TATE is an alternative treatment to the classical schemes in slow progressive metastatic/inoperable paraganglioma (PGL) and pheochromocytoma (PHEO). There is no consensus on which treatment to administer and/or the best sequence in patients who are candidates for both therapies. To clarify these questions, this systematic review assesses the prognostic value of [131I]MIBG and [177Lu]Lu-DOTA-TATE (PRRT-Lu) treatments in terms of progression-free survival (PFS) both globally and considering the primary location. Methods: This review was developed according to PRISMA Statement with 27 final studies (608 patients). Patient characteristics, treatment procedure and follow-up criteria were evaluated. In addition, a Bayesian linear regression weighted according to its sample size, and an alternative model which also included an interaction between the treatment and the proportion of PHEOs were carried out, adjusted by a Student's t distribution. Results: In linear regression models, [131I]MIBG overall PFS was, on average, 10 months lower when compared to PRRT-Lu. When considering the interaction between treatment responses and the proportion of PHEOs, PRRT-Lu showed remarkably better results in adrenal location. The PFS of PRRT-Lu was longer when the ratio of PHEOs increased, with a decrease in [131I]MIBG PFS by 1.9 months for each 10% increase in the proportion of PHEOs in the sample. Conclusion: Methodology, procedure and PFS from the different studies are quite heterogenous. PRRT-Lu showed better results globally and specifically in PHEOs. This fact opens the window to prospective trials comparing or sequencing [131I]MIBG and PRRT-Lu.